ANALISIS KEMAMPUAN PEMAHAMAN MATEMATIS MAHASISWA PADA MATA KULIAH KALKULUS - Myti Sandri; Rizkia Arafahnisa (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2023)
This aims study to analyze the mathematical comprehension ability of student in calculus course. Sample of research is student of informatics engineering at Universitas Mitra Karya. The type of research used is descriptive qualitative research. The data collection techniques used in this study included conducting preparatory activities, testing mathematical comprehension in the form of essays tested for validity, power, and difficulty index, collecting data, and distributing data. to analyze and draw conclusions. The instrument is a math comprehension test in the form of 5 text questions. The results of some math comprehension tests still show below average results. From this it can be concluded that students' understanding is still relatively low. As for the student’s difficulties in solved the problem of mathematical comprehension ability for indicators of identifying and making examples and not examples, changing one form of representation to another, and identifying the properties of a concept.